Comparação do planejamento em implantodontia por radiografia panorâmica e tomografia computadorizada de feixe cônico - ANDRADE, Wagner Almeida de (São Leopoldo Mandic, 2018)
The aim of this research was to evaluate the intra-examiner agreement in the planning of implant planning with panoramic radiography and cone beam computed tomography (CBCT). The research was a retrospective study of the 34 patients, in which panoramic radiography and CBCT were evaluated. The sample used in this study was 76 edentulous sites, with one or multiple spaces in different regions of the jaws, which performed the installation of implants. Inclusion criteria were patients attend in the period from 2013 to 2015, with panoramic radiography and CBCT, with the clinical planning, and discussed between students and teachers before the surgical procedure. The follow up of the patients who did not attend the inclusion were excluded. The radiographic and tomographic planning was compared with clinical planing. The experts answered a questionnaire with the indication of the area to be planned and type of implant, according to an interactive catalog. The data were analyzed in a descriptive statistic, and the intraclass correlation coefficient (ICC) was applied to evaluate the similarity between the measurements of the width and length of the implants by the computerized planning and the initial planning. The level of significance was 5%. The results showed that in the radiographic planning, the evaluation of the reproducibility using the CCI, the observed values were considered from average to good in the posterior maxillary. In tomographic planning, the anterior maxillary height coincided with the initial surgical planning; In the evaluation of the plans of the posterior maxillary and height of the posterior mandible, the CCI found were considered satisfactory. It was concluded that there were intra-examiner disagreements in the planning of the initial and tomographic implants. Cone beam computed tomography should be used in implant planning.